The impact of Exports and Imports on Economic Growth in Tanzania: The impact of Exports and Imports on Economic Growth in Tanzania - Hana MOUSSAOUI (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
The purpose of this study is to look into how trade has affected Tanzania's economic development. We utilize gross domestic product to measure economic growth and exports and imports to measure trade. (1) Is there a correlation between exports, imports, and economic growth? (2) Do those Variables have a long- or short-term relationship with one another? (3) Exist any causal links between the variables? (4) Which way does the causality run? Annual time series data from World Development Indicators (WDI) were used from 1962 to 2019. Vector auto regression models have been estimated using linear regression techniques. Our results showed that the VAR model was appropriate, and that GDP, exports, and differences were initially stationary. Our results showed that the VAR model was a suitable one, and that GDP, exports, and imports were stationary at initial differences but not at levels. As a result, the third series was merged of order two, and the first two series were integrated of order one. There was no long term equilibrium relationship between the three series, according to tests for cointegration, which show that the three variables were not co integrated. The causality test revealed that GDP was influenced by imports and exports. On the other hand; we discovered that exports and economic growth are causally related in just one direction. But there was a two-way causal relationship between GDP and imports. These findings show that exports and imports were regarded as the main drivers of economic growth in Tanzania.